From Stranded Praos ‘up to’ People Trailed by the Sea Stream: A Study about the Maritime Oral Tradition as a Source in the Writing about the Migration History in the Region of the Sawu Sea in the Lesser Sunda Islands - Didik Pradjoko (Journal of Maritime Studies and National Integration, 2017)
This research is about the migration history in the Sawu Sea Area, the Lesser Sunda Islands which made use of the oral tradition as its main source. For this purpose, this research can also be looked upon as a research in the maritime history which source is based on non-written sources. One can say that this topic has been much felt as not much important in the research on indigenous studies in particular in the areas outside Java so far. For this reason, this research is an effort to go beyond the conventional habit which is so far has been based on written sources (documents). In line with the applying of the oral tradition created a new genre the nonconventional historical genre which put the stress on the ‘mentalite’ of the people (society) which it studies. Although it is concerned with the local environment, this study also contributes to the national Indonesian history which it is hoped could strengthen the national integrity. The topic which has been studied is related to the process of migration and integration is a plural society in Sawu Sea area. The interaction between the society (people) and the people who came to this area from several areas of the islands of archipelago or nowadays Indonesia for sure have created social, economic, and cultural problems. These mentioned problems could be noticed in the oral tradition which is to be found everywhere in the area, from several oral stories which could be found everywhere in the area, one could know that the Sawu Sea area has developed into an area of the traffic and commerce, locally and regionally since hundred years ago. Methodological the oral sources played an important role as a source in written social history which has not developed and spread out its written culture.